Efektivitas Model Project Based Learning di Tinjau dari Kemampuan Berpikir Logis Mahasiswa Pada Materi Listrik Dinamis - Dwi Aprillia Setia Asih; Indica Yona Okyranida (UNIVERSITAS INDRAPRASTA PGRI, 2023)
The project based learning model can stimulate students to be more active, creative, responsible and able to think logically. The purpose of this study is to find out how the effectiveness of the project based learning model is viewed from students' logical thinking skills in dynamic electricity material. This research was conducted in the even semester of 2022/2023. The method used is a quasi-experimental method. Based on the results of the analysis and discussion that has been done, it can be concluded that there are significant differences in students' logical thinking abilities between the experimental class and the control class. This was reinforced by the results of the analysis of the independent sample T-test, namely the experimental class and the control class obtained a significance of 0.000 less than 0.005, in other words, there was a significant difference between the logical thinking abilities of the control class and the experimental class. Thus it can be concluded that the project based learning model in terms of the ability to think logically is effectively used in the learning process on dynamic electricity material.